Impact-Driven Energy Harvesting: Effect of Stress on Piezoelectric Bender - Abdal-Kadhim, Ali Mohammed; Leong, Kok Swee (Journal of Telecommunication, Electronic and Computer Engineering (JTEC), 2018)
This research is experimentally characterized and evaluates the effect of stress on a piezoelectric transducer by employing different bending mechanism. Three forms of bender: flat, unstressed, and pre-stressed are being investigated for their maximum electrical charge generation subjected to the applied stress. These mechanisms were fabricated using 3D printer where the piezoelectric beam can be inserted in to maximize the applied stress onto it. Variable impact forces are being exerted to bend the piezoelectric transducer for generating an electrical power across its terminals when connecting to an external load. In this respect, a rectangular shaped piezoelectric transducer with the size of (70X32X0.55) mm manufactured by Piezo System utilized to empirically study the relation between the impact force and the electrical output from the proposed piezoelectric bender. From the experimental results, the instantaneous AC volt output at open-circuit improved gradually and reached saturation of 10VAC, 50 VAC, and 70 VAC for flat, unstressed, and pre-stressed piezoelectric bender respectively. It is also found that the output power increases from 4mW of that recovered by using a flat mechanism to a double when using that an unstressed bending mechanism, while under the condition of pre-stressed, the electrical power further increases to 53mW at the same impact force.